2014
DOI: 10.1680/geolett.14.00036
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional characterisation of particle size and shape for ballast

Abstract: The size and shape of particles influence how effectively coarse angular aggregates of ballast interact. The aim of this study was to improve the characterisation of ballast particles using a threedimensional (3D) imaging method. Various size and shape indices, such as elongation ratio, sphericity and roundness, were determined from the scanned 3D images. A modified index called 'ellipsoidness' was proposed to capture adequately the shape of the 3D particles. Variation of these indices with particle size was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…This section summarizes reports from recent studies on a 3D assessment of particle size and shape where a 3D laser scanner has been utilized ( Figure 10). To facilitate 3D analysis, a modified index called 'ellipsoidness' E is proposed by Sun et al [40] and is shown in Figure 11.…”
Section: Effects Of Particle Angularity -Size and Shapesmentioning
confidence: 99%
“…This section summarizes reports from recent studies on a 3D assessment of particle size and shape where a 3D laser scanner has been utilized ( Figure 10). To facilitate 3D analysis, a modified index called 'ellipsoidness' E is proposed by Sun et al [40] and is shown in Figure 11.…”
Section: Effects Of Particle Angularity -Size and Shapesmentioning
confidence: 99%
“…However, the existing 3D roundness indexes usually do not involve corner identification and curvature evaluation [18,46]. In this study, we propose a novel method to evaluate 3D roundness based on local curvature values.…”
Section: Particle Roundnessmentioning
confidence: 99%
“…Lots of experimental and theoretical studies have been performed [1][2][3][4][5][6][7][8][9][10][11][12][13][14] to investigate the mechanical behaviour of granular soils. For example, Xiao et al [15] conducted a series of true triaxial tests on the rockfill material under drained loading condition.…”
Section: Introductionmentioning
confidence: 99%